2012
DOI: 10.1038/nmat3361
|View full text |Cite|
|
Sign up to set email alerts
|

Soft fibrin gels promote selection and growth of tumorigenic cells

Abstract: The identification of stem-cell-like cancer cells through conventional methods that depend on stem-cell markers is often unreliable. We developed a mechanical method of selecting tumourigenic cells by culturing single cancer cells in fibrin matrices of ~100 Pa in stiffness. When cultured within these gels, primary human cancer cells or single cancer cells from mouse or human cancer cell lines grew within a few days into individual round colonies that resembled embryonic stem-cell colonies. Subcutaneous or intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
462
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 404 publications
(495 citation statements)
references
References 41 publications
30
462
2
1
Order By: Relevance
“…17 These TRCs were generated by the previously reported soft 3D fibrin gel method. 5 About 1,250 tumor cells were mixed with 125 mL fibrinogen solution (2 mg/mL fibrinogen, activated by 0.5 units of thrombin) and seeded on 24-well plate. Adapting this method, we found that combination of Cis-MPs and LDI more effectively disrupted different types of TRCs (H22, CT26 and Lewis) ( Fig.…”
Section: Remodeling Macrophages By Combined Ldi and Cis-mps Is Explaimentioning
confidence: 99%
See 2 more Smart Citations
“…17 These TRCs were generated by the previously reported soft 3D fibrin gel method. 5 About 1,250 tumor cells were mixed with 125 mL fibrinogen solution (2 mg/mL fibrinogen, activated by 0.5 units of thrombin) and seeded on 24-well plate. Adapting this method, we found that combination of Cis-MPs and LDI more effectively disrupted different types of TRCs (H22, CT26 and Lewis) ( Fig.…”
Section: Remodeling Macrophages By Combined Ldi and Cis-mps Is Explaimentioning
confidence: 99%
“…Detailed methods are described as previously. 5 Tumor cells were detached from the standard culture conditions and suspended in culture medium (10% FBS) and cell density was adjusted to 10 4 cells/mL. Fibrinogen was diluted into 2 mg/mL with T7 buffer (pH 7.4, 50 mM Tris, 150 mM NaCl).…”
Section: D Fibrin Gel Culture Of Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Karpatkin first postulated that thrombin may trigger growth of dormant cancer cells [104], a notion of considerable importance given microscopic prevalence of ostensibly transformed cells in the adult and elderly population [105]. Contact with soft fibrin has also been proposed as a milieu that may enrich for CSCs [106].…”
Section: Coagulation System As Modulator Of Tumor Initiation Progresmentioning
confidence: 99%
“…[25,26] Our results sup port a previous report that a soft fibrin gel promoted the for mation of tumorigenic stem cell like colonies. [27] Although we observed increased proliferation and filopodial projection in the collagen fibrin composite matrix, rigidity alone is insufficient to explain the amplified fibroblast coculture effect with the collagen fibrin mixture. Another important factor that regulates cancer physiology in the TME is integrin receptor signaling of the cancer cells.…”
Section: Angiogenesismentioning
confidence: 59%